Profile of an occupation – hydraulic technician - Schambeck, Arne [Verfasser] (My University, 2024)
"As well as being important transport routes for both humans and goods, Germany’s many rivers provide places of recreation and valuable habitats. The job of hydraulic technicians is to take care of the maintenance of these navigation lanes and of other waterways. This occupational description sets out their tasks, points out the impacts climate change has on their work, and explains how trainee project developed from these." (author's abstract; BIBB-Doku)
Keywords: S 6.2.6 Hoch- und Tiefbauberufe; 370; Wasserbauer; Tätigkeitsmerkmal; Berufsbeschreibung; Klimaschutz